Optimisation models for GSM radio. (5th October 2005) - Mathar, Rudolf; Schmeink, Michael
The present paper contributes to the network planning methodology by introducing numerically tractable models for simultaneously optimising channel allocation and minimising interference in 2G networks. Furthermore, recent public concerns are included in the planning process by minimising electromagnetic exposition in sensitive areas. We successively subjoin constraints, and thus give a hierarchy of models of increasing complexity to cope with the growing requirements on modern GSM network planning.